2015
DOI: 10.3928/01477447-20150603-91
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Synovial Osteochondromatosis of the Hip

Abstract: Synovial osteochondromatosis is a benign metaplasia of the synovium resulting in the formation of osteocartilaginous nodules within the synovial lining. At presentation, radiographs typically reveal these nodules to have broken free from the synovial lining, becoming loose bodies residing in the free space of the affected joint. These fragments readily receive the necessary nutrients for continued growth from the synovial fluid in which they reside. Controversy exists over the management of the disease. Some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…8,9,21,22 Patients undergoing arthroscopic surgery tend to have a shorter stay in hospital, less postoperative pain, fewer complications, and faster recovery. 3,23 Our findings are similar to previous studies in that and we found arthroscopy for SC of the hip elicited good results.…”
Section: Discussionsupporting
confidence: 91%
“…8,9,21,22 Patients undergoing arthroscopic surgery tend to have a shorter stay in hospital, less postoperative pain, fewer complications, and faster recovery. 3,23 Our findings are similar to previous studies in that and we found arthroscopy for SC of the hip elicited good results.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to open surgery, arthroscopic surgery was associated with less invasiveness, decreased hospital stay, less postoperative pain, less surgical complications, and faster recovery. 10 17 18) Meanwhile, incomplete removal or recurrence is the concern of arthroscopic surgery because complete synovectomy is technically difficult. 11 19) When loose bodies remain, reoperation is possibly required for patients with persistent symptoms after the surgery.…”
mentioning
confidence: 99%